2021
DOI: 10.1186/s12866-021-02209-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of homologous Chinese soft-shell turtles (Pelodiscus sinensis) in different habitats

Abstract: Background Chinese soft-shell turtle (Pelodiscus sinensis) is an important commercial species for their high nutritional value and unique taste, but it has been a vulnerable species due to habitat loss. In this study, homologous juvenile turtles were allocated to lake, pond and paddy field to investigate the habitat effects on turtles. Results The growth, morphology and gut microbial communities were monitored during the 4 months cultural period. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 76 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…It is evident from the functional analysis result that overall, the gut microbiota of digestive functions in the three populations of M. terminalis presented differentiation by geographic isolation. A recent study clarifies that the gut microbiota is closely associated with host physiological metabolism, nutrient utilization, nutritional status, and health (Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is evident from the functional analysis result that overall, the gut microbiota of digestive functions in the three populations of M. terminalis presented differentiation by geographic isolation. A recent study clarifies that the gut microbiota is closely associated with host physiological metabolism, nutrient utilization, nutritional status, and health (Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the phylum Bacteroidetes is involved in the process of converting complex molecules into simpler compounds in anaerobic environments, it can convert complex polysaccharides into usable compounds and degrade organic pollutants (Rosselló-Mora et al 1999; Liu et al 2009). In addition, Proteobacteria and Bacteroidetes, as the dominant phyla, were detected in the gut of P. sinensis (Wu et al 2021). Thus, our results indicated that Proteobacteria and Bacteroidetes were the dominant phyla purifying the water of the two ponds throughout the entire culture periods.…”
Section: Bacterial Composition Of the Two Different Ponds At Three Sa...mentioning
confidence: 99%
“…Firmicutes was the dominant phylum in the aquaculture-reared species (Ramírez & Romero 2017; Klase et al 2019). For example, it appeared in the gut of P. sinensis from the greenhouse (Wu et al 2021). However, in our study, Firmicutes was the dominant phylum in the late stage of cultivation in both ponds, with its relative abundance being higher in pond B than in pond A (Fig.…”
Section: Bacterial Composition Of the Two Different Ponds At Three Sa...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese soft-shelled turtle ( Pelodiscus sinensis ) belongs to the genus Pelodiscus of the family Trionychidae, and it is recognized as an important economic species with nutritional value and medicinal value [ 1 , 2 , 3 ]. P. sinensis is widely distributed in East Asia, including China, Korea, Japan, and Vietnam [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%